2014
DOI: 10.1590/2176-9451.19.3.139-157.sar
|View full text |Cite
|
Sign up to set email alerts
|

From conventional to self-ligating bracket systems: Is it possible to aggregate the experience with the former to the use of the latter?

Abstract: IntroductionOrthodontics, just as any other science, has undergone advances in technology that aim at improving treatment efficacy with a view to reducing treatment time, providing patients with comfort, and achieving the expected, yet hardly attained long-term stability. The current advances in orthodontic technology seem to represent a period of transition between conventional brackets (with elastic ligatures) and self-ligating brackets systems. Scientific evidence does not always confirm the clear clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bóbbo 15 analyzed the torque of maxillary and mandibular incisor brackets, and Streva et al 14 Torque is related to the dental position desired at the end of treatment, and it must be individualized for the achievement of correct intercuspation, esthetics, and adequate function 14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Bóbbo 15 analyzed the torque of maxillary and mandibular incisor brackets, and Streva et al 14 Torque is related to the dental position desired at the end of treatment, and it must be individualized for the achievement of correct intercuspation, esthetics, and adequate function 14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, several techniques and devices have been recommended, including surgical procedures, vibration stimulation, greater use of individualized arches and brackets, as well as prescribing exodontia less frequently. 1,2 Self-ligating brackets (SLB) are orthodontic devices that unlike conventional brackets (CB) do not require elastomeric ligation methods or ligature wires to keep the arch in place. They were first presented by Stolzenberg in 1935 and were discovered as an accessory of the Russell attachment fabricated in the 1930s; however, it was not until the last 20 years that they have had their greatest use.…”
Section: Introductionmentioning
confidence: 99%
“…Transverse expansion with self-ligating systems is explained by low friction between the brackets and the archwires. 5 In the literature, some studies have indicated greater arch width increases with self-ligating brackets, 6 - 8 while other studies have shown no differences between self-ligating and conventional appliances. 9 - 11 It has been purported that the lower force produced by self-ligating brackets might lead to more stable treatment results.…”
Section: Introductionmentioning
confidence: 99%